Insights on Development from the Economics of Happiness - Graham, Carol (Oxford University Press on behalf of the World Bank, 2013)
The literature on the economics of happiness in developed economies finds discrepancies between reported measures of well-being and income measures. One is the so-called Easterlin paradox: that average happiness levels do not increase as countries grow wealthier. This article explores how that paradox and survey research on reported wellbeing in general can provide insights into the gaps between standard measures of economic development and individual assessments of welfare. Analysis of research on reported wellbeing in Latin America and Russia finds notable discrepancies between respondent assessments of their own wellbeing and income or expenditure based measures. Accepting a wide margin for error in both types of measures, the article posits that taking such discrepancies into account may improve the understanding of development outcomes by providing a broader view on wellbeing than do income or expenditure based measures alone. It suggests particular areas where research on reported well-being has the most potential to contribute. Yet the article also notes that some interpretations of happiness research psychologist set point theory, in particular may be quite limited in their application to development questions and cautions against the direct translation of results of happiness surveys into policy recommendations.